If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2+6g=2g-2
We move all terms to the left:
-2+6g-(2g-2)=0
We get rid of parentheses
6g-2g+2-2=0
We add all the numbers together, and all the variables
4g=0
g=0/4
g=0
| 23x+24=40 | | -5v-10=9+2v+9 | | 6(k+10)=-4(6k-12) | | 5x+4=5x-9 | | 4x+1=2(5-3x) | | 1/3(x+3/8)=12 | | 9+6m=5m | | 7/22p=1/11 | | -3-4g=-5g-10 | | 10y+4=6y-4 | | 6+c=-2+2c | | 4x+5+85+50=180 | | 6^(x-2)=96 | | 10y+8+5y=4y+3y-56 | | 9(2k+3)+2=11(k+1) | | 51=3n+9+n-2 | | x+0,2x=3372,25 | | -9r=-10r-8 | | 2=d+610 | | 9/18p=-27 | | -9r=-10r−8 | | 7x+21+9x=1 | | 11-5=3n-1-2n | | 10-9j=-10j | | x+0,2x=3000 | | 5x+2(2x+4)=44 | | x+0,2=3000 | | -y-2=2(y-2) | | 11-5n=3n-12-2n | | 10−9j=-10j | | 6-c=-15 | | 5(3x=1)=20 |